Evaluation of Education and Training Program Padangpanjang Social Organization for Youth Development - Yulmi Fitriza; Ramalis Hakim (Postgraduate School, Universitas Negeri Padang, 2022)
This study aims to evaluate the education and training program of the Padang Panjang Youth Development Social Institution (PSBR). The evaluation used is the CIPP model from Stufflebeam which is viewed from four aspects, namely: context, input, process and product evaluation aspects of the implementation of the Padang Panjang PSBR Education and Training program. The subjects of this study were the organizers, teachers, and participants of the Padang Panjang PSBR Training. Data collection techniques using observation, interviews, questionnaires and documentation studies. The results of the study show the following: Evaluation of the context (context) of the Padang Panjang PSBR training program has met the requirements in government regulations regarding the implementation of education and training. The results of the input evaluation based on the results of filling in the teacher's questionnaire obtained results with a level of conformity reaching 88%, the results of filling out the organizer's questionnaire with a level of conformity reaching 90%, the results of filling out the questionnaire for training participants with a level of conformity reaching 95%. The results of the evaluation process based on the results of filling in the teacher's questionnaire, it was found that the level of conformity reached 86%, the results of filling out the organizer's questionnaire with the level of conformity reached 87%. The results of filling in the training participant's questionnaire with a level of conformity reached 95.6%. Product Evaluation Results (results) of training participants Based on the results of filling in the teacher's questionnaire, the level of conformity reached 81%, the results of filling in the organizer's questionnaire with the level of conformity reached 84%. the results of filling in the training participant questionnaire with a conformity rate of 94%.